Apamarga Kshara Pratisarana To Manage Dushta Vrana : A Review - Suden, Akshay (International Research Journal of Ayurveda & Yoga, 2020)
Vrana is one of the most frequently occurring human ailment. If it is not properly and timely attended medically, it may lead to severe complications and may even transform into a dushta vrana due to aggravated vata, pitta, kapha & vitiated rakta doshas. Ayurvedic samhitas mention a series of measures for its cure. The review of the Ayurvedic samhitas and the research & review articles published in reputed journals show that dushta vrana ailment can be effectively cured with Apamarga kshara medication. Apamarga kshara possesses very useful and effective properties of chedana, pachana, lekhana, dahana, tridoshaghna vrana shodhak, dushta vrana ropaka,vilayana & stambhana etc. which assist in rapidly healing the dushta vrana. The medication of Apamarga kshara pratisarana should be adopted by the Ayurvedic medical practitioners to mitigate this ailment.